1990
DOI: 10.1111/j.1432-1033.1990.tb19355.x
|View full text |Cite
|
Sign up to set email alerts
|

myo‐Inositol oxygenase from rat kidneys

Abstract: myo-Inositol from rat kidneys, an oligomeric protein with apparent molecular mass of about 270 kDa can be dissociated under mild conditions to structured 16.8-kDa monomers. This dissociation can be reversed at high protein concentrations at room temperature. The corresponding apparent dimerization constant K,app =

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
2

Year Published

1994
1994
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 32 publications
0
1
2
Order By: Relevance
“…In addition, this analysis revealed that rMIOX did not dimerize on the addition of myoinositol or myo-inositol plus Fe# + \cysteine to the enzyme. This is in contrast with the substrate-dependent oligomerization reported previously [35] for the rat kidney native MIOX. An isoelectric focusing gel was run with two sets of standards (Sigma).…”
Section: Figure 5 Substrate Kinetics Of the Oxidation Of Myo-inositolcontrasting
confidence: 99%
See 2 more Smart Citations
“…In addition, this analysis revealed that rMIOX did not dimerize on the addition of myoinositol or myo-inositol plus Fe# + \cysteine to the enzyme. This is in contrast with the substrate-dependent oligomerization reported previously [35] for the rat kidney native MIOX. An isoelectric focusing gel was run with two sets of standards (Sigma).…”
Section: Figure 5 Substrate Kinetics Of the Oxidation Of Myo-inositolcontrasting
confidence: 99%
“…Thus there is a considerable discrepancy between the subunit molecular mass of the native enzyme from rat kidney (17 kDa) and the predicted value from the reported hypothetical rat transcript, which is approximately double the size [34]. Our results with pig rMIOX prove convincingly that the pig protein has a molecular mass of 32.7 kDa and, in contrast with Koller's observations [35,37,38], does not undergo oligomerization in the presence of myo-inositol.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation